2004
DOI: 10.1029/2003jd003803
|View full text |Cite
|
Sign up to set email alerts
|

Lower stratospheric densities from solar occultation measurements of continuum absorption near 2400 cm−1

Abstract: [1] Continuous absorption in the atmospheric window near 2400 cm À1 has been analyzed from infrared solar occultation spectra recorded by the Atmospheric Trace Molecule Spectroscopy (ATMOS) Fourier transform spectrometer at 0.01 cm À1 spectral resolution during its 4 shuttle flights between 1985 and 1994. The spring and autumn measurements were recorded over a wide range of temperatures and sulfate aerosol loadings. We used the ratio of the transmissions in microwindows at 2415 cm À1 and 2501 cm À1 as a measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The (N 2 ) 2 absorption in this wavelength region is dominated by CIA, but N 2 quadrupole line absorption, and absorption by true (N 2 ) 2 van der Waals molecules also contributes (Long et al 1973). The temperature and wavelength-dependent absorption coefficients for this primarily collisional feature have been measured empirically (Farmer & Houghton 1966;Lafferty et al 1996), and (N 2 ) 2 absorption has been observed in solar occultation (transmission) observations by Earthobserving satellites (Rinsland 2004), but, to our knowledge, it has never before been considered in the context of planet characterization from full-disk or transit transmission observations.…”
Section: Introductionmentioning
confidence: 87%
“…The (N 2 ) 2 absorption in this wavelength region is dominated by CIA, but N 2 quadrupole line absorption, and absorption by true (N 2 ) 2 van der Waals molecules also contributes (Long et al 1973). The temperature and wavelength-dependent absorption coefficients for this primarily collisional feature have been measured empirically (Farmer & Houghton 1966;Lafferty et al 1996), and (N 2 ) 2 absorption has been observed in solar occultation (transmission) observations by Earthobserving satellites (Rinsland 2004), but, to our knowledge, it has never before been considered in the context of planet characterization from full-disk or transit transmission observations.…”
Section: Introductionmentioning
confidence: 87%
“…The empirical expression chosen was inspired by the work of Rinsland et al, 25 where it was noted that the baseline in the region of N 2 ϩ CO 2 continua obeyed a consistent function of density for a diverse set of atmospheric conditions. For ACE-FTS processing we consider the ratio of the baseline at 2442.6 and 2502 cm Ϫ1 (denote this ratio as R b ).…”
Section: Low Altitudesmentioning
confidence: 99%
“…Collision‐induced absorption coefficients for N 2 (cm −1 atm −1 ) and their dependence with temperature have been reported for 2125 to 2600 cm −1 [ Lafferty et al , 1996, Table 1]. Continuum absorption by CO 2 also occurs in the window region, but its absorption is negligible in the 2500.6–2500.9 cm −1 interval selected for the current analysis [ Rinsland et al , 2004, Figure 2]. The window contains a weak CH 4 line at 2500.7616 cm −1 with a ∼5% line center absorption depth at 6.6 km tangent altitude.…”
Section: Retrievalsmentioning
confidence: 99%
“…As pointed out previously [ Foucher et al , 2009], two main difficulties for retrieving CO 2 from ACE spectra are: (a) accurate determination of the instrument pointing parameters (tangent heights) and (b) sensitivity of retrieved CO 2 to pressure/temperature profiles. Studies by Rinsland et al [2004] using atmospheric trace molecule spectroscopy (ATMOS) solar occultation FTS spectra recorded at 0.01 cm −1 resolution indicated that analysis of continuum pressure‐induced absorption by N 2 and CO 2 in the window region 2395–2525 cm −1 could help achieve the goal of precise determination of stratospheric densities from occultation measurements. Thus, we have implemented a procedure to determine the altitude shift to apply to version 2.2 ACE tangent heights as our means to resolve the difficulty (a) mentioned above.…”
Section: Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation